IMPLEMENTASI PROGRAM UPSKILLING DAN RESKILLING BERBASIS INDUSTRI DALAM PENINGKATAN KOMPETENSI GURU SMK NEGERI 1 CIAMIS: IMPLEMENTATION OF INDUSTRY-BASED UPSKILLING AND RESKILLING PROGRAMS IN IMPROVING THE COMPETENCE OF TEACHERS AT SMK NEGERI 1 CIAMIS - Nurdin, Nurdin; Juliani Musti Khofifah; Herlianto, Jajang Ikbal (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to analyze the upskilling and reskilling programs and their benefits in enhancing the competencies of vocational teachers at SMK Negeri 1 Ciamis in producing skilled graduates aligned with the demands of the business and industrial sectors. This research adopts a qualitative and descriptive approach. Sampling is based on the 3M principle (knowing, understanding, and experiencing), with 10 vocational teachers from SMK Negeri 1 Ciamis as informants. Data collection techniques include literature review, documentation, and structured and unstructured interviews. Data analysis involves data reduction, data presentation, conclusion, and verification stages. Additionally, method and source triangulation are employed to ensure data validity. The study results indicate that the upskilling and reskilling programs have successfully improved the quality of education at SMK Negeri 1 Ciamis. It was found that teachers feel more motivated and enthusiastic about carrying out their duties. Teachers' skills in implementing the latest technology in the learning process have increased, and they have an enhanced ability to foster student creativity through practical projects.